Mousque Cleaning Program in Improving Social Capital Development - Saputra, Rudia (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
When the Prophet sallallaahu 'alaihi wasallam migrated to Medina, the first step he took was to build a mosque which served as the main focus of the Muslim community at that time. The mosque, which is the center of the revival of the people, must be kept clean and pure. This study aims to describe the mosque's cleaning program in building social capital. Researchers limit this research to social capital by using descriptive qualitative research methods. In this case the researcher obtained data by interviews and documentation.